Contemporary perspectives on research on child development laboratory schools in early childhood education - Saracho, Olivia N. (Contemporary perspectives in early childhood education., 2019)
"Child development "laboratory schools are dedicated to research-based instruction and furthering innovation in education. Many of these schools are connected to universities, where students are able to benefit from university resources and best practices" (Khan, 2014). They have been in existence on university campuses for centuries in the United States. The earliest colonial colleges (e.g., Harvard, Yale, William and Mary, University of Pennsylvania) administered Latin schools or departments to prepare students for college (Good & Teller, 1973). Rutgers Preparatory School was founded in 1768 and was linked to the university until the 1950s (Sperduto, 1967). During the course of time, the laboratory schools have changed to meet the needs of the teaching professionals and have frequently guided the instructional methods to improve the science and art of teaching [International Association of Laboratory Schools (IALS), 2018]. They have also changed throughout the years from part-day, part-time programs (McBride, 1996, Myers & Palmer, 2017) to full-day care, some of which is inclusive of care offered through student service funds (Keyes, 1984; Shirah, 1988)"--